ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN TERBUKA KAB/KOTA DI DAERAH KHUSUS IBUKOTA DKI JAKARTA - Mega Azzahra, (2022)
The purpose of this research is to see the effect between the variables Gross Regional Domestic Product (GDRP), Total Population, Labor Force Participation Rate (LRPR), and Mean Years of Schooling (MYS) on the Open Unemployment Rate of DKI Jakarta Regency/City. In this study, the sample selected was the saturated sampling technique in the Regency/City of DKI Jakarta Province during the years 2011-2020. So the samples used in this study is 60 data obtained from the Badan Pusat Statistik (BPS) DKI Jakarta. This study uses panel data analysis by combining time series data and cross section data. The results partially show that the population has a significant negative effect on the Open Unemployment Rate, while the mean length of schooling has a significant positive effect on the Open Unemployment Rate, and LRPR and GRDP have no effect on the Open Unemployment Rate. The results of the study simultaneously show that GRDP, Total Population, LRPR, and MYS have an effect on the Open Unemployment Rate.